PERBANDINGAN PERILAKU MAHASISWA FAKULTAS KEDOKTERAN DAN FAKULTAS HUKUM UNIVERSITAS ANDALAS TERHADAP COVID-19 - Salshabilla, Miftah; Irfandy, Dolly; Hanum, Fathiya Juwita; Asterina, Asterina; Yetti, Husna (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Objective: To compare the behavior of Andalas University medical and law students towards COVID-19. Methods: This is an observational analytic study with a cross-sectional design. The sampling technique used proportional stratified random sampling with a sample size of 204 students of medical and law at Andalas University. The Data obtained are primary data collected using a questionnaire via google form which were then analyzed by bivariate analysis with the Mann-Whitney. Results: The results showed a statistically significant difference (p<0,05) between knowledge (p=0,00), attitude (p=0,045), and practices towards COVID-19 (p=0,038). Conclusion: This study shows that there are differences in the knowledge, attitudes, and practices towards COVID-19 between medical and law students.